Rancang Bangun Sistem Penggerak Pada GPR (Ground Penetrating Radar) - Lestari, Putri Cahaya; Erwin Renda Wardana; Rendy Muslim Arifin; Zaki Fadillah; , Rizky Augusta Gozzal; Barokatun Hasanah7 (Department of Electrical Engineering, UNJANI, 2025)
Ground Penetrating Radar (GPR) has become an essential tool in mapping and imaging subsurface features. However, to enhance precision and control in GPR usage, a GPR drive system utilizes stepper motor technology. The study focuses on the importance of precise control over GPR movement to improve scanning accuracy and image quality. By integrating stepper motors into the drive system, the research endeavors to enhance the precision, reliability, and efficiency of GPR in subsurface scanning. Through detailed design steps, the implementation of stepper motors aims to structurally and measurably control GPR movement. The design and construction of the GPR drive system using stepper motors aim to enhance precision and control in subsurface scanning. Through detailed design steps, the implementation of stepper motors aims to structurally and measurably control GPR movement. The design and construction of the GPR drive system using stepper motors aim to enhance precision and control in subsurface scanning. The integration of GUI and Arduino IDE in stepper motor control has proven effective, providing consistent and accurate control. Performance analysis indicates that stepper motors with A3967 drivers exhibit high accuracy, particularly in movements ranging from 0.5 to 2 cm, with insignificant errors. Stepper motors also demonstrate consistency across various speeds, while the direct relationship between pulse duration and duty cycle influences speed and position control with precision. Thus, the utilization of stepper motors in the GPR drive system improves precision, control, and image quality in subsurface scanning , supporting GPR applications in fields such as geology, archeology, and construction. Keywords : GPR, XY Coordinates, Stepper Motor, Automated drive system, Arduino IDE, and Scanning Precision